Activation of motility and chemotaxis in the spermatozoa - Manabu Yoshida; Kaoru Yoshida (Reproductive Medicine and Biology)
Abstract Background Sperm motility and chemotaxis are important early steps in the interaction between sperm and oocytes during fertilization. Understanding these processes is essential for their basic biological and clinical applications. This review outlines advances in understanding the molecular mechanisms of sperm activation and chemotaxis over the past two decades. Methods The review focuses on the molecular pathways of Ca2+ signaling and the role of the CatSper channel involved in this signaling, and examines the comprehensive mechanisms that regulate sperm motility in aquatic invertebrates, fish, and mammals. Main Findings Sperm are activated by environmental changes (e.g., pH and osmolality) and egg‐derived factors. CatSper channels mediate Ca2+ influx and regulate cell motility and chemotaxis. In addition to Ca2+, cAMP and membrane potential are also involved in the regulation of sperm motility. Alternative pathways exist in species lacking CatSper, highlighting the diversity of sperm activation mechanisms. Conclusion There has been significant progress in understanding sperm motility regulation mediated by Ca2+, notably with CatSper, but the molecular mechanisms of other factors remain unclear. Future research should focus on species lacking CatSper to uncover commonalities and diversity in sperm motility regulation using genome editing and transcriptomic analyses.